Non‐selective cation channel activity of aquaporin AtPIP2;1 regulated by Ca2+ and pH. (18th October 2016) - Byrt, Caitlin S.; Zhao, Manchun; Kourghi, Mohamad; Bose, Jayakumar; Henderson, Sam W.; Qiu, Jiaen; Gilliham, Matthew; Schultz, Carolyn; Schwarz, Manuel; Ramesh, Sunita A.; Yool, Andrea; Tyerman, Steve
Abstract: The aquaporin AtPIP2;1 is an abundant plasma membrane intrinsic protein in Arabidopsis thaliana that is implicated in stomatal closure, and is highly expressed in plasma membranes of root epidermal cells. When expressed in Xenopus laevis oocytes, AtPIP2;1 increased water permeability and induced a non‐selective cation conductance mainly associated with Na + . A mutation in the water pore, G103W, prevented both the ionic conductance and water permeability of PIP2;1. Co‐expression of AtPIP2;1 with AtPIP1;2 increased water permeability but abolished the ionic conductance. AtPIP2;2 (93% identical to AtPIP2;1) similarly increased water permeability but not ionic conductance. The ionic conductance was inhibited by the application of extracellular Ca 2+ and Cd 2+, with Ca 2+ giving a biphasic dose–response with a prominent IC50 of 0.32 mм comparable with a previous report of Ca 2+ sensitivity of a non‐selective cation channel (NSCC) in Arabidopsis root protoplasts. Low external pH also inhibited ionic conductance (IC50 pH 6.8). Xenopus oocytes and Saccharomyces cerevisiae expressing AtPIP2;1 accumulated more Na + than controls. Establishing whether AtPIP2;1 has dual ion and water permeability in planta will be important in understanding the roles of this aquaporin and if AtPIP2;1 is a candidate for a previously reported NSCC responsible for Ca 2+ and pH sensitive Na + entry into roots. Abstract : The paradigm that aquaporins may only allow permeation of neutral solutes has been challenged by examples of some animal aquaporins that can act as ion channels. Here, we reveal that AtPIP2;1 is permeable to both water and Na + in heterologous systems. The AtPIP2;1 ionic conductance is inhibited by low pH and Ca 2+ similar to previous observations for non‐selective cation channels indicating that AtPIP2;1 is a candidate for facilitating Na + flux across the plasma membrane of root cells and other cells that express PIP2;1, such as guard cells.